Pandemi Covid 19: Implementasi Insentif Pajak Bagi Wajib Pajak UMKM di Kabupaten Sumenep Belum Optimal - Putri, Fauziah Nirmala; Faisol, Moh. (Department of Accounting, Faculty of Economics & Business, 2022)
This research aims to identify and explain the implementation of the Minister of Finance regulation number 09/PMK.03/2021 regarding tax incentives for UMKM taxpayers affected by the 2019 coronavirus disease pandemic in Sumenep Regency in 2021. This study uses a qualitative descriptive approach with a case study method. Researchers conducted in-depth interviews (in-depth interviews) with two informants from the DJP and five informants of UMKM actors and were supported by the results of observations and documentation. The research data were analysed using Miller and Huberman qualitative data analysis, namely reduction, data presentation, conclusion, and data verification. The results show that the implementation of tax incentives in the Sumenep Regency is still not effective. This is because several UMKM that the researcher met claimed to have not taken advantage of, and did not even know about, the government having borne final income tax (DTP) incentives for UMKM taxpayers. This is because the socialization carried out by the DGT has not been received by the UMKM owners. After all, socialization is carried out through social media or posters and banners, and SMS because of PPKM. The hope is that the community is given direct socialization and even personally to each UMKM, however, this is understandable because the provision of these incentives coincides with the Covid-19 pandemic, in PPKM conditions. This research implies that direct socialization activities to UMKM, which are laypeople, are more informative and effective than through social media or online.